Managerial Decisions and Organizational Efficiency with Mediating Effect of Traditional Management Accounting Practices - Dahal, Rewan Kumar (Nepal Journal of Multidisciplinary Research, 2021)
The study envisioned looking at the magnitude of the managerial decisions (MDs) on organizational efficiency (OE) with intervening consequences of traditional management accounting practices (TMAPs) in Nepalese companies. The study's outcomes were depended on survey data gathered from 171 working representatives of the Nepalese manufacturing companies (NMCs). The reliability and validity of the analysis were performed by means of Cronbach's alpha, composite reliability (CR), and average variance extracted (AVE). The outcomes showed no significant intervening consequence of TMAPs in the relationship of MDs and OE. The study was limited to the NMCs and applied only one method of survey technique to gather data. No studies were found to show the connection between MDs and OE in NMCs. The study's outcome may further enhance OE if MDs are executed as a feature of an overall organizational strategy. The NMCs can utilize the study model as a rule to present another strategy that integrates MDs, TMAPs, and OE.